The inverted classroom in postgraduate teaching: Analysis of the teaching resources and their valuation by the students in the subject User behavior in digital environments - Rosser-Limiñana, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper presents the teaching strategies used to apply the flipped classroom model in the subject User behaviour in digital environments, (Universitary Master’s degree in Digital Communication) as well as some of the tools used, and the students’ evaluation of its application.After describing the methodology and resources used, a content analysis is carried out in order to identify the advantages and disadvantages of flipped classroom based on the evaluation made by the students.Conclusions are drawn on the repercussions of this methodology, both for the students and for the teacher, since it is a more applied way of training and learning, but it entails difficulties, especially derived from the effort involved in the change of role of teachers and students in its application.